Save me a seat - Weeks, Sarah 1955-; Varadarajan, Gita (Scholastic Press, 2016)
Ravi has just moved to the United States from India and has always been at the top of his class; Joe has lived in the same town his whole life and has learning problems...but when their lives intersect in the first week of fifth grade they are brought together by a common enemy (the biggest bully in their class) and the need to take control of their lives
Keywords: Einwanderer; East Indians -- United States -- Juvenile fiction; Immigrants -- United States -- Juvenile fiction; Adjustment (Psychology) -- Juvenile fiction; Learning disabled children -- Juvenile fiction; Bullying -- Juvenile fiction; Friendship -- Juvenile fiction; Elementary schools -- Juvenile fiction; East Indians; Learning disabilities; Bullying; Friendship; Schools; USA; Jugendbuch